Pemeriksaan Fisik Fungsi Panca Indra dan Edukasi Pencegahan Gangguan Fungsi Pada Anak Sekolah Dasar Kedungjaya - Erida Fadila; Sutrisno Sutrisno (Politeknik Kampar, 2023)
Physical examination of the function of the five senses and education on the prevention of functional disorders in elementary school children have the aim to make a positive contribution to the health of children at SDN Kedungjaya. This service aims to carry out physical examination activities for the function of the five senses and provide education to elementary school children about the prevention of functional disorders at SDN Kedungjaya. This community service method involves active participation from students and related parties in Kedungjaya and measurements of sight, hearing, smell, taste, and touch are carried out. The results of the examination are recorded and analyzed to identify any functional impairments in students. While education contains information about the importance of maintaining the health of the five senses and simple steps to prevent impaired function, such as maintaining hygiene, paying attention to a healthy diet, and avoiding exposure to risk factors that can damage the function of the five senses. Thus improving their quality of life.